2020
DOI: 10.1186/s13104-020-05246-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of PAX-8 in Sudanese patients diagnosed with malignant female reproductive tract tumors

Abstract: Objectives: Paired box protein-8 (PAX-8) immunohistochemical expression can be used as a diagnostic marker for epithelial cells tumors. This study aimed at investigating the immunohistochemical expression of PAX-8 among Sudanese females diagnosed with cervical, endometrial, and ovarian cancers between December 2017 and May 2019 by studying their Formalin-fixed paraffin embedded blocks. Results: Sixty patients diagnosed with female reproductive tract cancers were included who aged 58.7 ± 6.9 years (range, 43-71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that some members of PAX family are associated with the CC, 25,26 like PAX1. There was evidence suggesting that PAX1 methylation and HPV infection demonstrated the synergistic effects on the carcinogenesis of CC, 27 which activated multiple phosphatases and inhibited kinase cascades in CC 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that some members of PAX family are associated with the CC, 25,26 like PAX1. There was evidence suggesting that PAX1 methylation and HPV infection demonstrated the synergistic effects on the carcinogenesis of CC, 27 which activated multiple phosphatases and inhibited kinase cascades in CC 28 .…”
Section: Discussionmentioning
confidence: 99%
“…6 , 20 , 22 Adopting Pap smear as a screening tool for the early detection of CC in population-based screening programmes has successfully reduced the incidence of late CC by 85% in several developed countries over the past decades. 10 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…8 However, Sudan National cancer registry is inactive, and the only data source available is Khartoum Cancer Registry. 8 Therefore, records of cancer cases that existed are mainly obtained from hospitals and fragmented research reports, [9][10][11][12] making planning and implementing preventive and healthcare services towards CC challenging to achieve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PAX8 is considered to be an oncogene, which has the ability to regulate cell proliferation, cell growth, apoptosis and cell migration [ 9 ]. In addition, PAX8 + expression is associated with poor disease outcome in UCEC [ 10 ], but the molecular pathogenesis of PAX8 in UCEC is rarely explored, and its potential role in UCEC is mysterious. In this study, we found that PAX8 can interact with DDX5 protein to regulate downstream gene sets including ribosome, lysosome, ribosome biogenesis, and cell cycle.…”
Section: Introductionmentioning
confidence: 99%